Multi-centre assessment of nitroblue tetrazolium reactivity in human semen as a potential marker of oxidative stress. Issue 5 (May 2017) - Gosálvez, Jaime; Coppola, Lamberto; Fernández, Jose Luis; López-Fernández, Carmen; Góngora, Alfredo; Faundez, Ricardo; Kim, John; Sayme, Nabil; de la Casa, Moises; Santiso, Rebeca; Harrison, Keith; Agarwal, Ashok; et al.
Abstract: The nitroblue tetrazolium (NBT) reaction as a tracer of oxidative stress was examined in 707 ejaculates from seven clinics. Semen was initially surveyed by classifying the NBT reaction using a pre-established rank for the Oxisperm® test based on three colourimetric levels: L1, low ( n = 141 [20%]); L2, medium ( n = 538 [76%]) and L3, high ( n = 28 [4%]). L3 was indicative of a high level of superoxide anions. Halosperm® chromatin dispersion assay was used to analyse samples of ejaculates 30 min after ejaculation; no difference was found in DNA fragmentation of L1 or L3; L3 category semen samples incubated for 24 h at 37 o C showed a significantly faster rate ( P < 0.001) of DNA damage than those in L1. The NBT reaction was further characterized in the ejaculates of 100 patients to determine the relative contribution of seminal plasma, spermatozoa, or both. Seminal plasma was the most significant fraction of O2 − localization, whereas sperm fractions generated detectable reactive oxygen species in only 32% of the ejaculates. Formazan precipitates were primarily associated with the sperm mid-piece and seminal leukocytes; however, not all spermatozoa stained positive to formazan and not all leukocytes presented with equivalent production of superoxide anions.